River Tourism in the Douro Region - Pato, Lúcia (2017)
River Tourism presents itself as a recreational activity par excellence and as a new form of contact with heritage, history and culture, specially by observing the surrounding landscape (Prideaux, Timothy, & Cooper, 2009). It is the smallest boat speed, the feeling of tranquillity and the possibility to stop that make river tourism one of the ways to get to know the territories. The possibility to relive ancestral routes and activities should also be mentioned (Teles, 2012). In Portugal, one of the best examples of this type of tourism is presented in the Douro Region, by the river that gives it the same name (Douro), which is born in Spain and flows out to the sea of Oporto. Marked by a natural landscape and talents in cultural and historical terms, the Douro region was classified by Unesco as a World Heritage Site in 2001 as a living and evolving landscape, a remarkable testimony of cultural traditions, and practises and customs focused on viticulture (Aguiar, 2002). It is therefore not surprising that exists an increasingly high number of public and private initiatives for the development of the region. The region has been integrating global reference networks such as “National Geographic” and the “World Class Tourist Destination”, having also been considered the best river tourism destination in Europe (DouroValley, 2015). However, local people in the region have benefited very little with the existence of river tourism. Based on literature review and exploratory visits on the region, the aim of this study, therefore, is to explore a number of issues related to river tourism in Douro, raise awareness of the role that the Douro river plays in the development of the region and identify areas that require further research.